Development Of Career Decision Making Self Efficacy Tools In Indonesian Language - Rubiyanti, Yanti; Jatnika, Ratna; P. Siswadi, Ahmad Gimmy; Agustiani, Hendriati (UNIVERSITAS PAKUAN, 2023)
This study aims to develop a measuring instrument that can measure how self-confident adolescents are in making career decisions. This research uses a quantitative approach with a survey method. There were 262 young high school students in class XI SMA in Bandung Regency who filled out the Career Decision Making Self Efficacy (CDMSE) questionnaire . The Career Decision Making Self Efficacy measuring tool was adapted from the short form CDMSE measuring tool developed by Taylor and Betz (1996). Construct validity was carried out by confirmatory factor analysis using lisrel 8.8. The reliability of the measuring instrument uses the CR (Contract Reliability) value. The results of the confirmatory factor analysis of the measuring instrument show that the measurement model fits the data. Likewise with the reliability of this measuring instrument. Based on this, it can be said that the short form of the Career Decision Making Self Efficacy tool has good validity and reliability and can be used for adolescent subjects in Indonesia